Kekerasan Seksual Terhadap Perempuan dalam Novel "Perempuan yang Menangis Kepada Bulan Hitam" Karya Dian Purnomo: Kajian Wacana Kritis Sara Mills - Sri Yulianti; Andi Karman; Aslan Abidin; Usman Usman (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to examine the representation of sexual violence against women in Dian Purnomo’s novel *Perempuan yang Menangis Kepada Bulan Hitam* through Sara Mills’ critical discourse analysis approach. The study focuses on the positions of the subject, the object, and the reader in constructing the reality of the sexual violence experienced by the main character, Magi. This study employs a qualitative descriptive method with data collection techniques consisting of a literature review. The research data consists of quotations from the novel related to sexual violence, the marginalization of women, and forms of resistance by female characters. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that the subject position portrays Magi as a woman who possesses the awareness and courage to reject the practice of forced marriage and to fight for her right to her body and dignity. The object position reveals that Magi experiences marginalization due to the dominance of patriarchal culture, which positions women as powerless over their own lives. The reader’s position is shaped to foster empathy and critical awareness of the victim’s suffering, thereby guiding readers to critique cultural practices that harm women. This study contributes to strengthening the critical feminist discourse analysis framework of Sara Mills and provides insights into the representation of sexual violence and patriarchal culture in contemporary Indonesian literature